Inovasi Media Pembelajaran Kreatif untuk Meningkatkan Literasi dan Numerasi Siswa SDN 1 Gontoran - Nur Asmita Purnamasari; Hildah Dwipa Nurahma; M. Riki Aprianto; Nur Aulia Hidayatni; Nurul Latifah; Solatia Aprilia (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Low literacy and numeracy levels among elementary school students are a challenge in Indonesia's basic education system. The Teaching Campus Program implemented at SDN 1 Gontoran is one concrete effort to address this issue. Students participating in this program design and implement various creative learning media such as numeracy cards, smart boards, reading corners, reading cards, and educational posters. These activities are supported by a participatory and interactive approach that places students as active participants in the learning process. Pre-test and post-test results for fifth-grade students showed a significant improvement in literacy (from 24% to 73%) and numeracy (from 28% to 60%). This article presents the process of learning media innovation and its impact on improving student learning motivation and academic achievement. The addition of digital adaptation training such as Canva and Excel is also an important point to support 21st-century skills.